Vascular hemodynamics of the carotid bifurcation and its relation to arterial disease - Anayiotos, Andreas; Papaharilaou, Yannis (My University, 2013)
The hemodynamic hypothesis of atherosclerosis postulates that blood flow characteristics are a synergistic factor in the development of the disease in large arteries. This was first reported in 1968 by Fry1 who postulated that acute vascular endothelial damage is associated with increased blood velocity gradients and wall shear stress (WSS).
Keywords: Hemodynamics; Arterial disease; Atherosclerosis